Technical Guidance and Intellectual Property Rights Assistance ‘Sukamulya” Fruit Farmer Group Cirebon, West Java - Muafi Muafi; Siti Nursyamsiah; Fereshti Nurdiana Dihan; Tedy Setiawan Saputra; Ivan Piper (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community service aims to provide technical guidance and assistance on intellectual property rights to SMEs who are members of the